Barriers to Nutrition Intervention for Patients With a Traumatic Brain Injury: Views and Attitudes of Medical and Nursing Practitioners in the Acute Care Setting. Issue 2 (12th December 2017) - Chapple, Lee‐anne; Chapman, Marianne; Shalit, Natalie; Udy, Andrew; Deane, Adam; Williams, Lauren
Abstract: Background : Nutrition delivered to patients with a traumatic brain injury (TBI) is typically below prescribed amounts. While the dietitian plays an important role in the assessment and provision of nutrition needs, they are part of a multidisciplinary team. The views and attitudes of medical and nursing practitioners are likely to be crucial to implementation of nutrition to patients with TBI, but there is limited information describing these. Methods : A qualitative exploratory approach was used to explore the views and attitudes of medical and nursing practitioners on nutrition for patients with TBI. Participants at 2 major neurotrauma hospitals in Australia completed individual semi‐structured interviews with a set of questions and a case study. Interviews were transcribed and coded for themes. Results : Thirty‐four health practitioners participated: 18 nurses and 16 physicians. Three major themes emerged: (1) nutrition practices over the hospital admission reflect the recovery course, (2) there are competing priorities when caring for patients with TBI, and (3) the implementation of nutrition therapy is influenced by practitioner roles and expectations. Conclusion : Use of qualitative inquiry in the study of attitudes toward nutrition provision to patients with TBI provided detailed insights into the challenges of operationalizing nutrition therapy. These insights can be used to clarify communication between health practitioners working with patients with TBI across the continuum of care.